94.5k views
1 vote
2x-y=0; y=x-2

Substitution

2 Answers

0 votes

Answer:

Point form : (-2,-4)

Equation form : x=-2 , y=-4

Step-by-step explanation: Solve for the first variable in one of the equations, then substitute the result into the other equation.

Hope this helps you out! If you need anymore help with math, let me know and I will be more than happy to help you out! ☺

-Karleif Jonsi-

User Drodri
by
5.2k points
2 votes

Answer:

x=-2, y=-4. (-2, -4).

Explanation:

2x-y=0

y=x-2

------------

2x-(x-2)=0

2x-x+2=0

x+2=0

x=0-2

x=-2

y=-2-2=-4

User Ankit Tale
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.